Histopathologic insights into the mechanism of anti‐non‐Gal antibody‐mediated pig cardiac xenograft rejection. (20th September 2013) - Byrne, Guerard W.; Azimzadeh, Agnes M.; Ezzelarab, Mohamed; Tazelaar, Henry D.; Ekser, Burcin; Pierson, Richard N.; Robson, Simon C.; Cooper, David K. C.; McGregor, Christopher G. A.
Abstract The histopathology of cardiac xenograft rejection has evolved over the last 20 yr with the development of new modalities for limiting antibody‐mediated injury, advancing regimens for immune suppression, and an ever‐widening variety of new donor genetics. These new technologies have helped us progress from what was once an overwhelming anti‐Gal‐mediated hyperacute rejection to a more protracted anti‐Gal‐mediated vascular rejection to what is now a more complex manifestation of non‐Gal humoral rejection and coagulation dysregulation. This review summarizes the changing histopathology of Gal‐ and non‐Gal‐mediated cardiac xenograft rejection and discusses the contributions of immune‐mediated injury, species‐specific immune‐independent factors, transplant and therapeutic procedures, and donor genetics to the overall mechanism(s) of cardiac xenograft rejection.